Who is distressed? A comparison of psychosocial stress in pregnancy across seven ethnicities. Issue 1 (December 2016) - Robinson, Alexandra; Benzies, Karen; Cairns, Sharon; Fung, Tak; Tough, Suzanne
Abstract Background Calgary, Alberta has the fourth highest immigrant population in Canada and ethnic minorities comprise 28 % of its total population. Previous studies have found correlations between minority status and poor pregnancy outcomes. One explanation for this phenomenon is that minority status increases the levels of stress experienced during pregnancy. The aim of the present study was to identify specific types of maternal psychosocial stress experienced by women of an ethnic minority (Asian, Arab, Other Asian, African, First Nations and Latin American). Methods A secondary analysis of variables that may contribute to maternal psychosocial stress was conducted using data from the All Our Babies prospective pregnancy cohort (N =  3, 552) where questionnaires were completed at < 24 weeks of gestation and between 34 and 36 weeks of gestation. Questionnaires included standardized measures of perceived stress, anxiety, depression, physical and emotional health, and social support. Socio-demographic data included immigration status, language proficiency in English, ethnicity, age, and socio-economic status. Results Findings from this study indicate that women who identify with an ethnic minority were more likely to report symptoms of depression, anxiety, inadequate social support, and problems with emotional and physical health during pregnancy than women who identified with the White reference group. Conclusions This study has identified that women of an ethic minority experience greater psychosocial stress in pregnancy compared to the White reference group.